Analysis of fractal noise indicators in measuring systems of technical objects - Davydov, Viacheslav; Zmiivska, Vitalina; Shypova, Тetiana; Lysytsia, Dmytro (Technical University of Sofia, 2018)
The indicators and characteristics of the estimation of the noise fractality and interference in systems for measuring the characteristics and condition of technical objects are considered. A reasoned choice of indicators used in prospect for the implementation of the fractality estimation method is carried out.
Keywords: autocorrelation function; fractality index; statistical characteristics; reciprocally-correlative function; measuring; technical objects